Copy number variations of the ATP-binding cassette transporter ABCC6 gene and its pseudogenes - Kringen Marianne K (BMC Research Notes, 2012)
Abstract Background The ATP-binding cassette transporter ABCC6 gene is located on chromosome 16 between its two pseudogenes (ABCC6P1 and ABCC6P2). Previously, we have shown that ABCC6P1 is transcribed and affects ABCC6 at the transcriptional level. In this study we aimed to determine copy number variations of ABCC6, ABCC6P1 and ABCC6P2 in different populations. Moreover, we sought to study the transcription pattern of ABCC6 and ABCC6 pseudogenes in 39 different human tissues. Findings Genomic DNA from healthy individuals from five populations, Chinese (n = 24), Middle East (n = 20), Mexicans (n = 24), Caucasians (n = 50) and Africans (n = 24), were examined for copy number variations of ABCC6 and its pseudogenes by pyrosequencing and quantitative PCR. Copy number variation of ABCC6 was very rare (2/142; 1.4%). However, one or three copies of ABCC6P1 were relatively common (3% and 8%, respectively). Only one person had a single copy of ABCC6P2 while none had three copies. In Chinese, deletions or duplications of ABCC6P1 were more frequent than in any other population (9/24; 37.5%). The transcription pattern of ABCC6P2 was highly similar to ABCC6 and ABCC6P1, with highest transcription in liver and kidney. Interestingly, the total transcription level of pseudogenes, ABCC6P1 + ABCC6P2, was higher than ABCC6 in most tissues, including liver and kidney. Conclusions Copy number variations of the ABCC6 pseudogenes are quite common, especially in populations of Chinese ancestry. The expression pattern of ABCC6P2 in 39 human tissues was highly similar to that of ABCC6 and ABCC6P1 suggesting similar regulatory mechanisms for ABCC6 and its pseudogenes.